Untersuchungen der Fischbestände auf der Hatton Bank - Ehrich, Siegfried (1986)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010